Complement bridges between cells analysis of a possible cell-cell interaction mechanism (The Rockefeller University Press, 1977)
Different leukocytes (Raji, Daudi, Rael lymphoid cells; human peripheral blood lymphocytes, and guinea pig granulocytes), which had been coated with C3 by incubation of 37 degrees C for 20 min in a C3 solution, were demonstrated to form rosettes with erythrocytes coated with complement components (EAC142). The percentage of rosettes was dependent of the amount of C3 present on the cells. Loading of the lymphoid cells with C3 was a time- and temperature-dependent process. C3b was unable to serve the same purposes, although C3 and C3b occupied the C3 receptors on the lymphoid cells to a comparable degree. C3 functions in a similar manner. The C42 enzyme can be replaced by trypsin, so that bridging units may consist of C3 + C42, C5 + C42 OR C3 + trypsin, and C5 + trypsin. Bridging units can be constructed also from C4 + C1. It is suggested that enzymes on one cell liberate labile binding groups of complement components on adjacent cells, thus inducing coupling of the two cells. The possibility is raised that this type of cell interlinkage may play a role in vivo, since there is accumulating evidence that complement components are expressed in the plasma membrane of different cells.